A consensus approach: Understanding the support needs of women in Newport West, Wales, to participate in breast screening - Juping Yu; Sarah Wallace; Joyce Kenkre (Wiley, 2023)
Abstract Introduction Breast screening is an effective way to improve the early detection of breast cancer and reduce mortality. Unfortunately, low uptake of screening is often reported. This study aimed to explore the support needs of women residing in Newport West, Wales, to participate in breast screening. Methods Group Concept Mapping, a structured participatory consensus approach, was used as the method. Participants completed three activities either online or offline: brainstorming to generate statements, sorting statements into themed categories; rating statements for perceived importance and accessibility (easy to get). Results Thirty‐seven participants from seven ethnic groups took part. Sixty‐three statements (items of support) were generated and sorted into seven conceptually similar clusters (themes) (Trusting that I will be respected; Reassurance about my experience; Accessibility and convenience; Practical support; Addressing cultural diversity; Information tailored to individual needs; Raising awareness and understanding of breast screening). The 'Trusting that I will be respected' cluster was rated most important, while the 'Practical support' cluster was rated least accessible. Some disparity between responses was found based on ethnicity, language, disability and previous attendance of breast screening. Conclusions Women require a range of support to participate in breast screening. The results highlight the importance of ensuring women feel and are respected, instilling trust in the staff performing the screening, offering reassurance about positive experiences of breast screening and providing practical support, especially individualized/targeted support for people who do not speak and/or read English and those with a disability. Patient or Public Contribution The public contributed to the development of the information sheet, consent form, recruitment and data collection method.